Battery Management Module with Active Balancing and Cell Switching - Goksu, Omer Faruk; Acar Vural, Revna (IEEE, 2018)
The lithium ion type battery has become commercially more popular than the traditional battery and the usage market has increased. The main reason for this expansion and increase is that it has a high voltage value and a high energy density in a single cell. In addition to having these advantages, lithium ion batteries have usage limits. These limits are values such as operating voltage values, continuous current values, operating temperature. The use of battery cells outside the limits of use can shorten the life of the battery cells, leading to undesirable problems such as fire and explosion. These limits must be observed on the BMS and the operation of the battery cells within the safe limits must be guaranteed by the BMS. The proposed study includes a module design for battery management system that allows cell-based opening and closing of the battery pack and allows charging of the cells during use. The components have been chosen for low power consumption. The proposed structure is designed together with the charging unit. Power of module has been provided from its own battery cells. With the designed module and software, a battery pack with 8 battery cells can be created. Serial connected modules communicate with each other and can communicate with the user via serial communication if battery cell information is requested. It also decides on the charging of the series connected cells after the data received from all the modules. As a result of the tests made, it was seen that this module, which was created for the use of modular structures in BMS systems, increased the usage time of the battery pack. In addition, the low voltage level required for charging makes it possible to use many sources, from mobile phone adapters to solar energy, as a charging source.
Keywords: battery cell switching; lithium battery; modular structure; active battery management; Automation & Control Systems; Computer Science; Engineering